Decoding US investments for future battery and electric vehicle production. (May 2023) - Yang, Hong; Fulton, Lewis
Abstract: In just the last three years, since 2020, manufacturing plans for producing electric vehicles (EV) and batteries have surged. We relate them to four EV sales scenarios towards 2035 in the UC Davis Transportation Transition Model, with different EV shares of total light-duty vehicle sales. In each scenario, we estimate production capacities and investments needed. By comparing announced capacities to EV sales targets, we find that in the most ambitious scenario where US achieves 66% EV sales by 2030, the planned 5.1-million EV production falls short by over half; with tentative plans included, the gap closes to 4.6 million. In a less rapid scenario (40% by 2030), tentative plans are sufficient. Needed investments across these scenarios range from $20 to $143 billion, compared to current firm and tentative commitments of $75 to $108 billion, respectively. Investments will likely evolve to scale up production, increasing the chance of achieving higher-ambition targets.